Early Language Access and STEAM Education: Keys to Optimal Outcomes for Deaf and Hard of Hearing Students - Marie Coppola; Kristin Walker (Education Sciences)
This paper offers an overview of a large study of language and cognitive development in deaf and hard of hearing children. Specifically, we investigated how acquiring a signed or spoken language (language modality) and when a child’s access to language begins (i.e., at birth or later in development) influence cognitive development. We conducted in-person behavioral assessments with 404 children 3–10 years old (280 deaf and hard of hearing; 124 typically hearing). The tasks measured a range of abilities along a continuum of how strongly they depend on language input, such as general vocabulary and number words (strongly dependent) vs. skills such as tracking sets of two to three objects and standardized ‘nonverbal’ picture-similarity tasks (relatively independent of language). Overall, the timing of children’s access to language predicted more variability in their performance than language modality. These findings help refine our theories about how language influences development and suggest how a STEAM pedagogical approach may ameliorate the impacts of later access to language. These results underscore children’s need for language early in development. That is, deaf and hard of hearing children must receive fully accessible language input as early as possible through sign language, accompanied by hearing technology aimed at improving access to spoken language, if desired.